The Requirement for US28 During Cytomegalovirus Latency Is Independent of US27 and US29 Gene Expression - Krishna, Benjamin A.; Wass, Amanda B.; Sridharan, Rajashri; O'Connor, Christine M. (Frontiers in Cellular and Infection Microbiology, 2020)
The ability to establish a latent infection with periodic reactivation events ensures herpesviruses, like human cytomegalovirus (HCMV), lifelong infection, and serial passage. The host-pathogen relationship throughout HCMV latency is complex, though both cellular and viral factors influence the equilibrium between latent and lytic infection. We and others have shown one of the viral-encoded G protein-coupled receptors, US28, is required for HCMV latency. US28 potentiates signals both constitutively and in response to ligand binding, and we previously showed deletion of the ligand binding domain or mutation of the G protein-coupling domain results in the failure to maintain latency similar to deletion of the entire US28 open reading frame (ORF). Interestingly, a recent publication detailed an altered phenotype from that previously reported, showing US28 is required for viral reactivation rather than latency, suggesting the US28 ORF deletion impacts transcription of the surrounding genes. Here, we show an independently generated US28-stop mutant, like the US28 ORF deletion mutant, fails to maintain latency in hematopoietic cells. Further, we found US27 and US29 transcription in each of these mutants was comparable to their expression during wild type infection, suggesting neither US28 mutant alters mRNA levels of the surrounding genes. Finally, infection with a US28 ORF deletion virus expressed US27 protein comparable to its expression following wild type infection. In sum, our new data strongly support previous findings from our lab and others, detailing a requirement for US28 during HCMV latent infection.